Young People Hopes for The Future after Digital Disruptions and the Covid-19 Pandemic - Kristiyani, Titik (Universitas Ahmad Dahlan, 2024)
The uncertainty caused by disruptions, exacerbated by the emergence of the Covid-19 pandemic, has influenced how young people perceive their future. This research aimed to explore young people's hopes for the future through a qualitative, phenomenological approach, involving 390 participants aged 18-25 years. Data were collected via a survey with open-ended questions and interviews, and analyzed using thematic content analysis. The findings revealed that young people's hopes center around three key factors: personal factors such as career success, education, selfdevelopment, emotional and material well-being, and leisure; interpersonal relationship factors, mainly focused on family; and broader environmental factors, including social concerns and global development. To support young people in navigating future uncertainties, it is recommended to enhance educational and career guidance programs to build resilience, strengthen mental health support, foster community engagement, and promote global awareness initiatives that empower young adults to address social and environmental challenges.